Challenging neck mass: non-functional giant parathyroid adenoma. (17th August 2016) - Mossinelli, Chiara; Saibene, Alberto Maria; De Pasquale, Loredana; Maccari, Alberto
Abstract : A 46-year-old man was referred to our ear, nose and throat department after the accidental discovery of a large retrotracheal mass. In order to obtain the diagnosis and to plan treatment he underwent a full battery of tests (CT, MRI, blood tests, hormonal assays, ultrasounds, thyroid scintigraphy, urine tests and fine-needle aspiration of the mass), but none of these was able to define the true nature of such cervical mass. Only after surgical excision and histological evaluation, it was diagnosed as an exceptional case of giant non-functional parathyroid adenoma.